Historia bloku mieszkalnego jako koncepcji antropologicznej - Mioduszewska, Zofia (Kultura i Społeczeństwo, 2009)
This analysis is a chronological presentation of the proposals for architecture that would solve the problem of housing for the masses as well as concepts that influenced the designs of post-war housing estates — from patronage housing estate and the 19th century utopian ideas (phalanstery) through 20th century concepts of a neighbourhood unit (social housing estate), up to a modern block of flats. The prototypes of blocks of flats were on the one hand the first workers’ housing estates and the spatial concepts created by utopian socialism, and on the other the social housing realized in the 1930s, in line with the principles declared in the Athens Charter and during the International Congresses of Modern Architecture.